Internalisasi Nilai Kearifan Lokal Budaya Jawa dalam Kode Etik Akuntan - Muhammad Aras Prabowo; Mariska Nur Hanifah; Muhammad Abduh; Ummu Kalsum; Jefriyanto Jefriyanto (Wahana Riset Akuntansi, 2023)
Purpose – This study aims to internalize the local wisdom values of Javanese Ojo dumeh culture, Javanese Kromo, Sungkan, Eling Waspada, Alon-alon Asal Kelakon, and Rukun Agawe Santoso in accounting practice so that they can become guidelines in enforcing the accountant's code of ethics in Javanese society.Design/methodology/approach – This research is a literature study in the field and sub-fields of Javanese Culture and the code of ethics of accountants in the 2019-2023 period which consists of 223 international and national articles. Data analysis used is descriptive qualitative analysis.Findings – The results of the research show that the local wisdom values of Javanese culture Ojo Dumeh, Javanese Kromo, Sungkan, Eling Waspada, Alon-alon Asal Kelakon, and Rukun Agawe Santoso are aligned with the eight accountant codes of ethics. By internalizing and applying these values, an accountant is able to understand the importance of maintaining integrity and upholding ethical values in professional life.Originality/value – This research compares the literature on the field and sub-sectors of Javanese Culture and the code of ethics of accountants, so that it is able to explore the values of Javanese culture more comprehensively. Then internalized into the accountant's code of ethics.Research limitations/implications – This research is only at the stage of internalizing Javanese cultural values Ojo dumeh, Javanese Kromo, Sungkan, Eling, and Waspada, Alon-alon Asal Kelakon, and Rukun Agawe Santoso in the accountant's code of ethics. It needs to be developed up to the implementation stage of the accountant's code of ethics based on Ojo dumeh, Javanese Kromo, Sungkan, Eling, and Waspada, Alon-alon Asal Kelakon, and Pillars of Agawe Santoso in the accounting profession.